Correction to: A Universal Principle to Accurately Synthesize Atomically Dispersed Metal–N4 Sites for CO2 Electroreduction - Zheng, Wanzhen; Chen, Feng; Zeng, Qi; Li, Zhongjian; Yang, Bin; Lei, Lecheng; Zhang, Qinghua; He, Feng; Wu, Xi‑Lin; Hou, Yang (Nano-Micro Letters, 2020)
Atomically dispersed metal–nitrogen sites-anchored carbon materials have been developed as effective catalysts for CO2 electroreduction (CO2ER), but they still suffer from the imprecisely control of type and coordination number of N atoms bonded with central metal. Herein, we develop a family of single metal atom bonded by N atoms anchored on carbons (SAs–M–N–C, M = Fe, Co, Ni, Cu) for CO2ER, which composed of accurate pyrrole-type M–N4 structures with isolated metal atom coordinated by four pyrrolic N atoms. Benefitting from atomically coordinated environment and specific selectivity of M–N4 centers, SAs–Ni–N–C exhibits superior CO2ER performance with onset potential of − 0.3 V, CO Faradaic efficiency (F.E.) of 98.5% at − 0.7 V, along with low Tafel slope of 115 mV dec−1 and superior stability of 50 h, exceeding all the previously reported M–N–C electrocatalysts for CO2-to-CO conversion. Experimental results manifest that the different intrinsic activities of M–N4 structures in SAs–M–N–C result in the corresponding sequence of Ni > Fe > Cu > Co for CO2ER performance. An integrated Zn–CO2 battery with Zn foil and SAs–Ni–N–C is constructed to simultaneously achieve CO2-to-CO conversion and electric energy output, which delivers a peak power density of 1.4 mW cm−2 and maximum CO F.E. of 93.3%. Highlights: 1 A family of SAs–M–N–C consisted of carbon nanosheets supported atomic sites of isolated metal atom coordinated with four pyrrolic N atoms was fabricated. 2 The SAs–Ni–N–C exhibited superior electrochemical CO2 electroreduction (CO2ER) activity and selectivity.